Мільман Перрі, Альберт-Бейтс Лорд та Джон-Майлс Фоули: що нам робити з ними - Детелич, М. (Народна творчість та етнологія, 2012)
Formulae of the South Slavic oral epic songs can be divided into three categories: 1) the true formulas, which are the oldest syntactic patterns that connect epics with other oral literary genres as well as connect the different layers within one and the same genre; 2) the rudimentary formulas which are in fact common places as white throat (even in an Arab), white dawn/day, green sword, etc. similar to the Homeric formulae; 3) formulae in the making, named by J.-M. Foley as «generic formulas», meaning by that moveable and changeable strings of words that can easily fit the asymmetric epic decasyllable verse (4+6). Within a given epic body all three types of formulae can exist at the same time, so it is often possible to track the development of a formula from a string of words to its full, closed form. U slučaju južnoslovenske deseteračke epike, formule se mogu podeliti na tri glavna tipa: 1) najstarije i potpune – prave – formule čija je važnost najveća jer deluju i linearno (povezujući epiku sa drugim usmenim žanrovima) i vertikalno(uspostavljajući vezu među slojevima različite dubine); 2) delimično formirane – rudimentarne – formule (opšta mesta kaobelo grlo Arapovo, bela zora / zorica, beli dan, crna zemlja, zelen mač itd.), vrlo slične homerskim; 3) formule u nastajanju, ono što –D.-M. Foli označava kao «generičke formule», a što su zapravo pokretni i promenljivi nizovi reči prilagođeniasimetričnoj podeli epskog deseterca (4+6). U jednom istom epskom korpusu sva tri tipa formula postoje istovremeno te je vrlo često moguće pratiti nastanak i razvoj prave formule od slogovnog niza do njen pune, zatvorene forme.